Perbandingan Kinerja Pilar Jembatan Menggunakan Metode Direct Displacement Based Design Dan Capacity Spectrum Method - Ockto Perry P Harahap; Zulfikar Djauhari; Alex Kurniawandy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The structure usually design base on the elastic analysis that would be multiplied by load factor to simulate the ultimate condition. Actually the behavior of building subject to seismic load are in-elastic. Evaluation to assess inelastic condition of the building during the earthquake are required to obtain assurance that a satisfactory performance . Analysis and performance evaluation can be done with the concept of performance-based seismic design. In this study, there are two performance-based analytical methods used, the method of Direct Displacement-Based Design (DDBD) and Capacity Spectrum Method (CSM). Structures analyzed in this research are the bridge pier with seismic load plan by RSNI 2833:201X. Value of displacement, base shear force, effective time, and damping produced by the method DDBD will be compared with the CSM. Result of analysis by the method of DDBD is the greatest displacement target, that is 0.7304 m, while the displacement by the method of CSM is 0,027 m. Base shear forces (V), results of DDBD, have 265.98 kN smaller than the CSM. However, the effective damping (ξeff) and effective time (Teff), the results of the analysis DDBD, have greater value when compared with the results of the analysis of CSM. Performance evaluation pier structures with DDBD method shows the structures are at the level of that exceed the limit structure stability which indicate that the structure stability has huge risk to collapse in an earthquake. In CSM Method, pillar structure is in Operational category which indicates that there was no structural and non-structure damage on piers when earthquake happened.Keyword : Earthquake, pier structure, Direct Displacement-Based Design, Capacity Spectrum Method, performance